Students’ perception on the use of social media in enhancing vocabulary - Abraham, Najwa Syah (Maliki Interdisciplinary Journal, 2024)
Digital era now on, many students interested in social media than learning manually. Using some social media platforms that make enjoy environment to students’ give positive impact in enhancing English vocabulary. This research aim to explore the impact of the use social media to enchance English vocabulary’s students from students perceptions. The analysis from trancripted interviews about the social media platforms most used and helping to enhancing vocabulary.